New paleomagnetic data from the northern Puna and western Cordillera Oriental, Argentina: A new insight on the timing of rotational deformation - Prezzi, Claudia Beatriz (2004)
Along the Central Andes a pattern of vertical axis tectonic rotations has been paleomagnetically identified. The rotations are clockwise in southern Bolivia, northern Chile and northwestern Argentina. Various models have been proposed to explain the geodynamic evolution of the Central Andes, but the driving mechanism of these rotations remains controversial. Constraining the spatial variability and the timing of the rotations may contribute to a better understanding of their origin. Our results complement information from previous studies, improving the knowledge of tectonic rotations in the region of the northern Argentine Puna and western Cordillera Oriental. In the San Juan de Oro basin (SJOB), 132 cores were drilled from the middle Miocene Tiomayo Formation in the zone of Tiomayo-Santa Ana (22°30′S-66°30′W), and from the ∼17 Ma Casa Colorada dacite dome complex. Another 114 cores were collected from middle Miocene dacitic dome centers emplaced in the zone of Laguna de Pozuelos basin (22°30′S-66°00′W). The results of our paleomagnetic study suggest that the sampled zones underwent very low, statistically insignificant rotation since middle Miocene. However, a tendency for low magnitude rotation appears when observing our data together with paleomagnetic results from coeval rocks in neighbouring areas. If so, this low rotation could be related to middle Miocene thrust activity in the central and eastern parts of the Cordillera Oriental. The combined analysis of paleomagnetic and structural data illustrates the probable, direct relationship between timing of significant rotations and timing of local deformation in the sourthern Central Andes.